2015
DOI: 10.1002/jbio.201500112
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of photodynamic therapy and irrigants in disinfection of root canals

Abstract: In this study, the combined effects of photodynamic therapy and irrigants in eradicating common endodontic pathogens are evaluated. Roots of 80 extracted single rooted teeth are divided into 2 groups (1) mechanical flushing; (2) antibacterial irrigation. After cleaning and shaping, they are inoculated with either (A) Streptococcus mutans or (B) Enterococcus faecalis and incubated. They are again subdivided and either only irrigated or irrigated and lased. Dentin shavings are taken from root canal walls and cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
(43 reference statements)
0
23
0
8
Order By: Relevance
“…Many authors demonstrated the positive effect of PDT on E. faecalis reduction on extracted human teeth when it was accompanied by various protocols [25][26][27][28][29]. Some authors demonstrated that the effect of PDT in combination with various antimicrobial irrigants (NaOCl and EDTA) was more pronounced against E. faecalis, while the effect of irrigants alone was greater against Streptococcus mutans [25]. Others demonstrated that repeated PDT cycles enhanced the positive effect of PDT from 45% of E. faecalis reduction to 95% and emphasized that the most effective antibacterial protocol is still the conventional chemo-mechanical debridement [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors demonstrated the positive effect of PDT on E. faecalis reduction on extracted human teeth when it was accompanied by various protocols [25][26][27][28][29]. Some authors demonstrated that the effect of PDT in combination with various antimicrobial irrigants (NaOCl and EDTA) was more pronounced against E. faecalis, while the effect of irrigants alone was greater against Streptococcus mutans [25]. Others demonstrated that repeated PDT cycles enhanced the positive effect of PDT from 45% of E. faecalis reduction to 95% and emphasized that the most effective antibacterial protocol is still the conventional chemo-mechanical debridement [30].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm is typically recalcitrant to conventional antibiotic treatment, which generally aims to kill pathogenic microbes or block biofilm production [163]. A common clinical application of APDT of S. mutans is therefore disinfection of root canals [164]. In addition to their cariogenicity, S. mutans has been implicated in more severe conditions, including cerebral microhemorrhage [165] and infection of heart valves as well as atheromatous plaques in blood vessels [166].…”
Section: Streptococcus Mutans (Gram-positive)mentioning
confidence: 99%
“…A infecção endodôntica ocorre com a proliferação de bactérias no interior dos canais radiculares que adentraram nesse meio através da exposição do dente ao ambiente oral, devido a lesões cariosas ou traumáticas, causando a formação de lesões perirradiculares persistentes 1,2 . Dessa forma, o tratamento endodôntico deve ser realizado como medida para eliminar e inativar os biofilmes bacterianos e seus subprodutos facilitando assim a reparação dos tecidos apicais 1,3 .…”
Section: Introductionunclassified
“…Dessa forma, o tratamento endodôntico deve ser realizado como medida para eliminar e inativar os biofilmes bacterianos e seus subprodutos facilitando assim a reparação dos tecidos apicais 1,3 . Durante o preparo químico mecânico utiliza-se instrumentos manuais ou mecanizados, concomitante a irrigação com substâncias químicas, e em alguns casos, o uso de medicação intra-canal entre as sessões clínicas, obtendo assim relativas taxas de sucesso na diminuição da quantidade de bacté-rias presentes nos canais radiculares 2,4,5,6 . Está bem evidenciado na atual literatura, que a desinfecção completa dos canais radiculares é bastante difícil, devido à diversidade dos sistemas de canais radiculares na região apical onde há maior predomínio de deltas apicais e formação de biofilme extraradicular, o que dificulta a eliminação de micro-organismos resistentes, tal como o Enterococcus Facaelis 5,7,8 .…”
Section: Introductionunclassified
See 1 more Smart Citation